Chronic fluoxetine treatment alters the structure, connectivity and plasticity of cortical interneurons. (30th April 2014) - Guirado, Ramon; Perez-Rando, Marta; Sanchez-Matarredona, David; Castrén, Eero; Nacher, Juan
Abstract: Novel hypotheses suggest that antidepressants, such as the selective serotonin reuptake inhibitor fluoxetine, induce neuronal structural plasticity, resembling that of the juvenile brain, although the underlying mechanisms of this reopening of the critical periods still remain unclear. However, recent studies suggest that inhibitory networks play an important role in this structural plasticity induced by fluoxetine. For this reason we have analysed the effects of a chronic fluoxetine treatment in the hippocampus and medial prefrontal cortex (mPFC) of transgenic mice displaying eGFP labelled interneurons. We have found an increase in the expression of molecules related to critical period plasticity, such as the polysialylated form of the neural cell adhesion molecule (PSA-NCAM), GAD67/65 and synaptophysin, as well as a reduction in the number of parvalbumin expressing interneurons surrounded by perineuronal nets. We have also described a trend towards decrease in the perisomatic inhibitory puncta on pyramidal neurons in the mPFC and an increase in the density of inhibitory puncta on eGFP interneurons. Finally, we have found that chronic fluoxetine treatment affects the structure of interneurons in the mPFC, increasing their dendritic spine density. The present study provides evidence indicating that fluoxetine promotes structural changes in the inhibitory neurons of the adult cerebral cortex, probably through alterations in plasticity-related molecules of neurons or the extracellular matrix surrounding them, which are present in interneurons and are known to be crucial for the development of the critical periods of plasticity in the juvenile brain.